Constitution and Armed Forces in the XXI century: National defense and human security - Cea Cienfuegos, Sergio; Coronado Donoso, Ricardo (Derecho Público Iberoamericano, 2018)
In the 21st century and from a constitutional perspective, the Armed Forces should maintain the role of the National Defense and replace the National Security with the Human Security, it being considered necessary to maintain a general mention to the career and Military Justice, indicating the purposes and principles that govern them. For such purposes, the american constitutional texts that allude to the subject are analyzed comparatively.